2020
DOI: 10.1002/gps.5449
|View full text |Cite
|
Sign up to set email alerts
|

Preventing depression among older people living in rural areas: A randomised controlled trial of behavioural activation in collaborative care

Abstract: Objectives This study aimed to test if a behavioural activation (BA) programme was more effective than usual care at reducing the risk of conversion to major depression over 52 weeks among adults aged 65 years or older living in rural Western Australia. Secondary aims were to test if participants assigned to the BA intervention experienced greater decline in the severity of depressive and anxiety symptoms than older adults treated with usual care over 26 and 52 weeks, as well as greater improvement in physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Other uses included treatment plan management (n=9) [ 18 , 21 - 26 , 30 - 32 , 38 , 41 , 42 , 111 ], rehabilitation services (n=3) [ 20 , 37 , 43 , 44 ], and social support (from health care personnel; n=2) [ 15 , 17 ]. Telephone initiatives were used predominantly for education, follow-up evaluation, and care support (n=20) [ 47 , 50 , 54 , 58 - 62 , 97 - 103 , 105 , 107 , 109 - 113 ]. Telemonitoring interventions (with or without an additional attached device to measure physiological data) were used to record and monitor progress (n=18) [ 80 , 83 - 89 , 93 - 101 , 103 ], as alert or reminder systems (n=10) [ 80 , 83 - 88 , 93 , 94 , 96 ], and for strength training [ 89 - 92 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other uses included treatment plan management (n=9) [ 18 , 21 - 26 , 30 - 32 , 38 , 41 , 42 , 111 ], rehabilitation services (n=3) [ 20 , 37 , 43 , 44 ], and social support (from health care personnel; n=2) [ 15 , 17 ]. Telephone initiatives were used predominantly for education, follow-up evaluation, and care support (n=20) [ 47 , 50 , 54 , 58 - 62 , 97 - 103 , 105 , 107 , 109 - 113 ]. Telemonitoring interventions (with or without an additional attached device to measure physiological data) were used to record and monitor progress (n=18) [ 80 , 83 - 89 , 93 - 101 , 103 ], as alert or reminder systems (n=10) [ 80 , 83 - 88 , 93 , 94 , 96 ], and for strength training [ 89 - 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…All but one of these virtual care delivery models yielded either comparable or similar or better health or behavioral outcomes compared with in-person care or other comparators (videoconference: 4/4; telephone: 10/11; telemonitoring: 4/4; web-based: 7/7; app: 2/2). Examples of outcomes measured include emergency visits [ 51 , 84 , 85 ], hospitalization [ 51 , 61 , 84 , 85 , 93 ], quality of life [ 25 , 43 , 49 , 53 , 61 , 75 , 84 , 85 ], mortality [ 21 , 22 ], physical activity or strength [ 43 , 49 , 60 , 64 , 89 ], health literacy [ 46 , 56 , 58 , 73 , 75 , 78 , 79 , 84 , 85 , 93 ], and measures of anxiety or depression [ 47 , 53 , 61 , 66 - 70 ]. Telephone-based coaching was not effective in preventing falls but improved physical activity compared with those receiving unrelated health information [ 60 ], while a telephone-based telerehabilitation study noted worse physical activity versus waitlist control [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 606 reports were screened by title and abstract, and 32 articles were identified. After the full-text screening, six eligible RCTs were identified [18][19][20][21][22][23] . When the reference lists of these studies for this review were audited, no extra RCTs that met the inclusion criteria were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 displays the characteristics of the eligible studies. The participants were young individuals (four studies) [18][19][20][21] and older individuals (two studies) 22,23) . Mental disorders included depression 18,20,22) , mental health symptoms 19) , insomnia 23) , and schizophrenia 21) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation